2005
DOI: 10.1161/01.str.0000155734.34652.6c
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Measures of Chronic Periodontitis and Carotid Artery Plaque

Abstract: Background and Purpose-Chronic periodontitis (CP) is associated with stroke and subclinical atherosclerosis, but clinical measurement of CP can be time consuming and invasive. The purpose of this study was to determine whether radiographically assessed CP is associated with nonstenotic carotid artery plaque as an ultrasound measure of subclinical atherosclerosis. Methods-Panoramic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
74
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 41 publications
6
74
0
Order By: Relevance
“…For example, subjects with severe periodontitis have decreased flow-mediated dilation of the brachial artery (17), increased carotid artery intima-media thickness (18,19), and a nearly 4-fold increased risk for the presence of carotid artery plaque (19). Periodontal inflammation has been shown to decrease the antiatherogenic potency of HDL (20) and to enhance lipopolysaccharide-mediated macrophage activation (21).…”
mentioning
confidence: 99%
“…For example, subjects with severe periodontitis have decreased flow-mediated dilation of the brachial artery (17), increased carotid artery intima-media thickness (18,19), and a nearly 4-fold increased risk for the presence of carotid artery plaque (19). Periodontal inflammation has been shown to decrease the antiatherogenic potency of HDL (20) and to enhance lipopolysaccharide-mediated macrophage activation (21).…”
mentioning
confidence: 99%
“…After adjustments for age, race/ethnicity, gender, education, body mass index, smoking, diabetes, systolic blood pressure, and LDL and HDL cholesterol, it was demonstrated that periodontal bacterial burden was related to the carotid IMT, a measure of subclinical atherosclerosis (P=0.002). In other investigations, using a multivariate logistic regression model, periodontal bone loss was associated with a ~ 4-fold increase in risk for carotid atherosclerosis (adjusted OR, 3.64; CI, 1.37 to 9.65) (Engebretson et al, 2005) and edentulousness was independently associated with the risk of aortic stenosis in a cohort of 2341 individuals (Volzke et al, 2005). Using seroepidemiology, a study of 572 patients showed that the extent of atherosclerosis (using coronary angiography, carotid duplex sonography, and ankle-arm index) and CVD mortality were associated with elevated IgA and IgG titers to infectious agents.…”
mentioning
confidence: 81%
“…These three studies chosen among a number of studies illustrate that systemic inflammation can be initiated by common oral bacteria causative of periodontal infection and can induce several changes in the circulation that induces changes in the vasculature that are very closely related to known processes of cardiovascular disease development. Carotid artery plaque but not brachial-ankle pulse wave velocity [45,[62][63][64][65][66] has been found to be a valid association. Desvarieux et al [65] report how clinical probing depth and assessment of periodontal bacterial species relate to changes in the carotid intermedia thickness (IMT) during a threeyear average follow-up.…”
Section: Intermediary Factors and Biomarkers For Cvdmentioning
confidence: 95%